Unique root anatomy of mandibular second premolars: clinical strategies for effective disinfection and preservation of dentine structure in root canal treatment—a case report - Jeong, Ji Wook; Gonzalez, Erika Silguero; Makins, Scott R.; Kirkpatrick, Timothy (Frontiers in Dental Medicine, 2024)
It is difficult to predict the outcomes of non-surgical root canal treatment (NSRCT) for mandibular second premolars with multiple root canals. In these teeth, the complicated anatomy with fin(s), or a C-shape, and possible secondary canal(s) varies unpredictably. The morphology of the root canals provides shelters for bacteria to remain, regrow, and form biofilms in spite of the endodontic treatment. Moreover, the prevalence of mandibular second premolars with multiple canals is extremely infrequent. Therefore, the clinical managements of NSRCT in such cases are not sufficiently reported. This case report introduces two cases of NSRCT for mandibular second premolars with a radicular groove and also presents the appropriate clinical strategies and techniques. Cone-beam computed tomographic imaging (CBCT) was used preoperatively. After the completion of NSRCT, CBCT was reused to review the completed procedures using the Nerve Canal tool in CS 3D Imaging v3.2.9 and v3.8.7. Five canals were obturated in Case 1, and four canals in Case 2 along with a C-shape morphology. Analyzing the configuration of the root canals by CBCT was critical to achieve successful NSRCT because the numbers, exits, configurations, and volumes of the secondary canals were not anticipated after reviewing 2D radiographs. Based on the interpretation, the advanced protocols of NSRCT were planned: First, augmentation of chemo-mechanical cleaning, but minimizing the loss of dentine. Second, the tactile examination to locate and negotiate the orifices of the secondary canals. Lastly, the optimized plan and technique for root canal filling of the complex canal systems. Considering the predictability of the outcomes of NSRCT, there are three independent variables for the prognosis of the treatment; Anatomy of the root canal system, Bacterial population and Clinical strategy and performance.